Analisis SWOT Terhadap Pelaksanaan Bauran Pemasaran (Marketing Mix) Pada Lembaga Pendidikan Prima Mandiri Utama Palangka Raya - Fendy Hariatama (FKIP, Universitas Palangka Raya, 2021)
This research focuses on the marketing strategy, which is one of the principle activities done by companies in their effort to secure and enhance the longevity of their business. It also creates and enhances the demands made by consumers. Therefore, increasing sell revenue and making more profits from it. In their effort to get maximum profits, the companies must be able to run the center point of marketing mix. The best way to do it is by applying the SWOT analysis – which stands for strength, weakness, opportunities, and threats – to each of the variable in the marketing mix. The research uses descriptive qualitative method. This method is applied to an educational institution called “prima mandiri utama”. There are three steps in acquiring the data, namely: observation, interview, and documentation. Next, the activities within the institution is discussed and analyzed. The validity of the data is strengthened by the further exploration of other sources which are taken from numerous important individuals, namely: the president director, HR manager, the academic manager marketing coordinators and staffs, also the students and parents. The research shows that the marketing mix in “Prima Mandiri Utama” is still unbalance; this can be seen from the SWOT analysis of the seven variables which do not get an even attention. Some variables get neglected whereas some other is being overly done. Nonetheless, the marketing mix strategy in “Prima Mandiri Utama” has been very well done; this can be seen from mobile implementation of it, the institution does not imitate the rival companies, they are also managed to comprehend the situation around the institution although the future planning is not significant yet.